The Function of Education in Cultivating an Anti-Corruption Mindset Among Youth at SMA APIPSU Medan - Karolina Sitepu; Khairun Na’im; Donny Setha; Dahris Siregar; Mospa Darma; Indah Sari Liza Lubis; Cut Rafyqa Fadhilah; Reny Khaerany Nisfiary; Karina Mia Berutu; Puji Chairu Sabila (LKP KARYA PRIMA KURSUS, 2026)
Education is instrumental in the development of an anti-corruption mindset among the younger generation, which serves as the groundwork for the eradication of corruption in Indonesia. This movement is a reflection of the government's political will and is bolstered by the thorough preparation and readiness of legal instruments. This legal counseling activity is designed to foster a profound comprehension of the perils of corruption, to foster a sense of collective awareness, and to inculcate the importance of integrity in the minds of high school students and the general public. The Community Based Research (CBR) method was implemented through a series of stages, including joint planning (identification of school needs and material preparation), participatory implementation (outreach, legal quizzes, Q&A, small group discussions), and reflective evaluation (pre-post understanding survey). This process involved active collaboration between the service team, teachers, and students. With the participation of 30 eleventh-grade students, accompanying teachers, and facilitators from various lecturers and students in the study programs at Universitas Tjut Nyak Dhien Medan, this activity was conducted on May 9, 2026, at SMA APIPSU Medan. The outcome was a substantial improvement in the participants' comprehension of the detrimental effects of socio-economic corruption, as well as a dedication to honesty, transparency, care, and independence. The interactive dynamics enabled participants to compare societal corruption (cheating, extortion) with school corruption cases (cheating, extortion) and develop practical prevention strategies. In summary, this participatory CBR approach has demonstrated its efficacy in the development of a generation of youth who are highly integrity-driven. This is achieved through collaborative anti-corruption education in school environments, which not only strengthens the understanding and commitment of participants to the principles of honesty and transparency, but also validates the importance of the education-based anti-corruption movement in the establishment of a sustainable anti-corruption ecosystem in Indonesia.